210 - Palliative Care in Dementia: Continuous palliative sedation in nursing home residents with dementia suffering from extreme refractory neuropsychiatric symptoms. (October 2020) - Veldwijk-Rouwenhorst, Annelies E.; Smalbrugge, Martin; Zuidema, Sytse U.; Hanssen, Suzan A.J.; Koopmans, Raymond T.C.M.; Gerritsen, Debby L.
Abstract : Introduction: Extreme neuropsychiatric symptoms (NPS) can be a heavy burden for nursing home (NH)-residents, relatives and caregivers. When conventional treatments are ineffective or have intolerable side effects, extreme NPS can be considered refractory. In these situations, continuous palliative sedation (CPS) is sometimes administered. We explored the trajectory leading to CPS and its application in NH-residents with dementia and refractory NPS. Methods: A qualitative interview study was performed in 2017. Relatives, elderly care physicians and other staff members involved with three NH-residents with dementia and extreme refractory NPS who received CPS were interviewed. These NH-residents lived on dementia special care units of three NHs in the Netherlands. We used consecutive sampling to select participants. Medical files were studied. Semi-structured interviews were conducted. Transcriptions were analyzed with thematic analysis, including directed content analysis. Results: Nine in-depth interviews with fourteen participants were held. Analysis resulted in five main themes with several subthemes reflecting phases of the trajectory leading to CPS and the CPS application itself, a sixth main theme concerned evaluations thereof. According to the first theme (run-up), the suffering of the NH-resident was described as unbearable/an inner struggle. Participants still had hope for improvement. Concerning the second theme (turning point), hope was lost, participants were convinced they had tried everything and experienced feelings of powerlessness and failure. Regarding theme three (considering CPS), intermittent sedation was applied in all three cases and peer consultation was employed. Honoring the wish of the NH-resident and therapeutic uncertainties, among others, were important subthemes. According to theme four (decision to start CPS), in each case one specific aspect was a decisive trigger for administering CPS. Concerning theme five (applying CPS) feelings of relief were experienced after starting with CPS. Conclusions: The trajectory leading up to CPS in NH-residents with dementia and extreme refractory NPS was complex and burdensome, but the application led to relief and contentment of all those involved. We recommend to include external consultation in the decision process and to apply intermittent sedation as a preceding step when CPS is considered.